2017
DOI: 10.4172/2252-5211.1000259
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the Environmental Implication of Management Options for Municipal Solid Waste in Nigeria

Abstract: In te rnationa l J o u rn al of W a s te R esource s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A study by Obadina [57] found that the reuse of some waste material is possible, however Odewumi [58] noted that they have been under-utilised. Incineration, on the other hand, is not commonly practiced in Lagos and Nigeria as a whole [59]. It is against this backdrop that this study assessed construction material waste disposal methods that are based on seven methods, including landfill, burning, recycling, reuse as backfill, on site dig and bury, open dumping, and incineration identified from the literature.…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Obadina [57] found that the reuse of some waste material is possible, however Odewumi [58] noted that they have been under-utilised. Incineration, on the other hand, is not commonly practiced in Lagos and Nigeria as a whole [59]. It is against this backdrop that this study assessed construction material waste disposal methods that are based on seven methods, including landfill, burning, recycling, reuse as backfill, on site dig and bury, open dumping, and incineration identified from the literature.…”
Section: Background Of the Studymentioning
confidence: 99%
“…These construction projects were purposively selected based on their level of completion, availability, and involvement of construction professionals. The firms were categorised into small, medium, and large based on their annual turnover, as adopted by previous studies [59][60][61][66][67][68]. Furthermore, company characteristics, such as ownership status, age, size, and area of specialisation were adopted for this study.…”
Section: Research Participantsmentioning
confidence: 99%
“…Owoeye & Rotowa [13] recommended the use of an engineering landfill device for waste disposal to discourage open dumping. Kofoworola [14] reported a significant reduction of greenhouse gas emissions resulting from the current MSW management of open dumping and burning with the implementation of disposal strategies such as sanitary landfill with gas capture.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing population and the attendant human activities have geometrically led to increasing waste tonnage since the creation of Ekiti State in October 1996 and the establishment of the state capital at Ado-Ekiti. The use of controlled sanitary landfills is desirable to mitigate the adverse effects of open dumping and burning and ultimately safeguard public health and the environment [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This balance and working of the environment is often threatened by anthropogenic activities resulting to various undesirable consequences [2,3]. A notable consequence of the human activities is waste generation and consequent poor waste management [4][5][6]. Severally, these wastes generated defile the natural degradation processes and often upset the natural ecosystem balance.…”
Section: Introductionmentioning
confidence: 99%